Same goals, different challenges: A systematic review of perspectives of people with diabetes and healthcare professionals on Type 2 diabetes care. Issue 9 (11th July 2021) - Catapan, Soraia de Camargo; Nair, Uthara; Gray, Len; Cristina Marino Calvo, Maria; Bird, Dominique; Janda, Monika; Fatehi, Farhad; Menon, Anish; Russell, Anthony
Abstract: Aims: To identify the views of people with Type 2 diabetes (PWD) and healthcare professionals (HCP) about diabetes care. Methods: A systematic review of qualitative studies reporting both groups' views using thematic synthesis frameworked by the eHealth Enhanced Chronic Care Model was conducted. Results: We searched six electronic databases between 2010 and 2020, identified 6999 studies and included 21. Thirty themes were identified with in general complementary views between PWD and HCP. PWD and HCP find lifestyle changes challenging and get frustrated when PWD struggle to achieve it. Good self‐management requires a trustful PWD–HCP relationship. Diabetes causes distress and often HCP focus on clinical aspects. They value diabetes education. PWD require broader, tailored, consistent and ongoing information, but HCPs do not have enough time for providing it. There is need for diabetes training for primary HCP. Shared decision making can mitigate PWD's fears. Different sources of social support can influence PWD's ability to self‐manage and PWD/HCP suggest online peer groups. PWD/HCP indicate lack of communication and collaboration between HCP. PWD's and HCP's views about quality in diabetes care differ. They believe that comprehensive, multidisciplinary and locally provided care can help to achieve better outcomes. They recognise digital health benefits, with room for personal interaction (PWD) and eHealth literacy improvements (HCP). Evidence‐based guidelines are important but can detract from personalised care. Conclusion: We hypothesise that including PWD's and HCP's complementary views, multidisciplinary teams and digital tools in the redesign of Type 2 diabetes care can help with overcoming some of the challenges and achieving common goals.